Cost Analysis of Volar Plate Fixation Versus Plaster Cast Immobilization for Intra-Articular Distal Radial Fractures. (3rd November 2021) - Selles, C.A.; Mulders, M.A.M.; van Dieren, S.; Goslings, J.C.; Schep, N.W.L.
Abstract : Background: The aim of this study was to compare the cost-effectiveness and cost-utility between plaster cast immobilization and volar plate fixation for acceptably reduced intra-articular distal radial fractures. Methods: A cost-effectiveness analysis was conducted as part of a randomized controlled trial comparing operative (volar plate fixation) with nonoperative (plaster cast immobilization) treatment in patients between 18 and 75 years old with an acceptably reduced intra-articular distal radial fracture. Health-care utilization and use of resources per patient were documented prospectively and included direct medical costs, direct non-medical costs, and indirect costs. All analyses were performed according to the intention-to-treat principle. Results: The mean total cost per patient was $291 (95% bias-corrected and accelerated confidence interval [bcaCI] = −$1, 286 to $1, 572) higher in the operative group compared with the nonoperative group. The mean total number of quality-adjusted life-years (QALYs) gained at 12 months was significantly higher in the operative group than in the nonoperative group (mean difference = 0.15; 95% bcaCI = 0.056 to 0.243). The difference in the cost per QALY (incremental cost-effectiveness ratio [ICER]) was $2, 008 (95% bcaCI = −$9, 608 to $18, 222) for the operative group compared with the nonoperative group, which means that operative treatment is more effective but also more expensive. Subgroup analysis including only patients with a paid job showed that the ICER was −$3, 500 per QALY for the operative group with a paid job compared with the nonoperative group with a paid job, meaning that operative treatment is more effective and less expensive for patients with a paid job. Conclusions: The difference in QALYs gained for the operatively treated group was equivalent to an additional 55 days of perfect health per year. In adult patients with an acceptably reduced intra-articular distal radial fracture, operative treatment is a cost-effective intervention, especially in patients with paid employment. Operative treatment is slightly more expensive than nonoperative treatment but provides better functional results and a better quality of life. Level of Evidence: Economic and Decision Analysis Level I . See Instructions for Authors for a complete description of levels of evidence.